El incremento del IVA en la comercialización de artículos de ferretería en el segundo semestre del 2016 en la ciudad de Riobamba - Chauca Saeteros, Robinson Gonzalo (2018)
"THE INCREASE OF VAT IN THE COMMERCIALIZATION OF ARTICLES OF HARDWARE IN THE SECOND SEMESTER OF 2016 IN THE CITY OF RIOBAMBA", ABSTRACT: "THE INCREASE OF VAT IN THE COMMERCIALIZATION OF ARTICLES OF HARDWARE IN THE SECOND SEMESTER OF 2016 IN THE CITY OF RIOBAMBA", is a quantitative, quantitative research that started from the identification of the study problem and the current situation according to the reform of June 13, 2016, which applies the Value Added Tax (IVA) in the marketing of hardware items, based on the information clearly defined both the general and specific objectives, therefore the state of the art helped to strengthen the results that include characteristics and concepts related to the subject of study and research. For its development we used the deductive and analytical method that was applied with emphasis to the recognition of the problem and the general knowledge of the variables. The type of research was descriptive and field while the design was not experimental. The population and the sample were selected based on the cadastre of the ruc provided by the official page of the Internal Revenue Service of the authorized taxpayers for the commercialization of hardware items of the year 2016, the data collection was done through a survey that allowed to define the respective conclusions and recommendations complying with the study objectives that allowed to elaborate and determine how the IVA increase affects two percentage points in the sale of hardware in its sales and in the collection of taxes in the canton Riobamba in 2016; knowing that they are feasible which indicates that there is a reduction of 3.92% of tax collection in relation to the year 2015.